Risks in Bank Credit Agreements in Relation to Consumer Protection - Dany, Bina Era (Judge : Jurnal Hukum, 2024)
As financial intermediary institutions, banks have an important role in the national development process, which arises from the main business activities of banks, namely attracting funds directly from the community in the form of savings and returning them to the community. Building local communities in the form of credit. To receive a loan from a bank, consumers must apply for a loan to the bank themselves. Questions arise regarding what risks may arise from bank loan contracts and what actions can be taken to protect customers from risks arising from bank loan contracts. The research method used in this paper is normative legal research, namely the study of legal sources, both primary legal sources and secondary legal sources. The results of the examination show that there are many relief clauses in bank loan contracts which can burden the customers themselves, and the dominant market position of the bank at the time the loan is granted is This shows that the customer has no other choice. Because, at the contract point, debtor customers are usually very dependent on credit support from the bank. It is hoped that this can be achieved through Consumer Protection Law Number 8 of 1999 and Law Number 21 of 2011 concerning the Financial Services Authority. can protect customers on credit agreements.